High Uptake in Schneiderian Papillomas of the Maxillary Sinus on Positron-Emission Tomography Using Fluorodeoxyglucose - Lin, F.Y. (AJNR Am J Neuroradiol, 2009)
SUMMARY: Schneiderian papillomas are benign tumors of the nasal cavity and paranasal sinuses often asymptomatic in their early stages. We report a case of a maxillary sinus oncocytic schneiderian papilloma first detected by positron-emission tomography by using fluorodeoxyglucose (FDG). Schneiderian papillomas demonstrate increased FDG uptake, similar to that of other oncocytic tumors, making it important for otolaryngologists and radiologists to realize that high uptake of FDG does not necessarily indicate a malignant lesion.